No end in sight yet for the global food price crisis - Glauber, Joseph W.; Hernandez, Manuel A.; Laborde Debucquet, David; Martin, Will; Rice, Brendan; Vos, Rob (International Food Policy Research Institute, 2023)
After the sharp rise in international prices of wheat and other staple foods in the wake of Russia’s February invasion of Ukraine, since May prices have fallen back to pre-war levels. Has the global food price crisis now come to an end? Unfortunately, such a conclusion is premature. Domestic food prices for consumers continue to rise in most countries. Meanwhile, ongoing uncertainties — not the least of which is the continuing war — au gur continued turmoil in global food markets. Global food security remains at high risk; hundreds of millions of people already face acute food insecurity and their numbers are rising, according to the Global Report on Food Crises. In this blog post, we try to disentangle the main factors in play. Given the importance of both Russia and Ukraine as suppliers in global markets for wheat, maize, sunflower seeds and oil, and Russia’s importance in international fertilizer and energy markets, the war provoked a surge in food and energy prices worldwide. The Food and Agriculture Organization (FAO)’s international food price index climbed to its all-time high in mid-May (Figure 1). At that point, wheat prices, for instance, were up 32% from their level at the start of the war. Then prices fell, with those of agricultural commodities, including wheat, returning to pre-war levels. However, prices remain high by historical standards, reflecting impacts of supply disruptions and the surge in global demand for commodities during the recovery from the COVID-19-induced recession in 2021.